Assessing the policy shift of Bilateral Investment Treaties from traditional North-South to new models of South-South investment : implications for South Africa and the Global South - Isike, Christopher (University of Pretoria, 2025)
Thesis (PhD (International Relations)--University of Pretoria, 2025.